O enriquecimento ilícito por patrimônio incompatível de agentes públicos no direito sancionador anticorrupção - Gomes, Denis Dela Vedova (2021)
The present work aims to analyze the legal treatment given to the illicit enrichment of public agents, through the incompatible patrimony with their remuneration, evaluating the international commitments assumed by Brazil on the subject and the implications of the matter regarding the fundamental rights of the citizen, trying to compound different views to optimize the protection of the juridical asset with due legal process in its formal and material sense. Public sector probity requires the appropriate exercise of the powers conferred by law to public agent for the purpose of justification. The illicit enrichment by incompatible patrimony, by dispensing the identification of the conduct, although, requires that the prosecution conduct previous investigation about patrimonial evolution to proof that conduct represents misuse of power, risking to neglect the proper protection of the juridical asset in detriment of the presumption of innocence